2012
DOI: 10.1115/1.4006610
|View full text |Cite
|
Sign up to set email alerts
|

HP Vane Aerodynamics and Heat Transfer in the Presence of Aggressive Inlet Swirl

Abstract: Modern lean burn combustors now employ aggressive swirlers to enhance fuel-air mixing and improve flame stability. The flow at combustor exit can therefore have high residual swirl. A good deal of research concerning the flow within the combustor is available in open literature. The impact of swirl on the aerodynamic and heat transfer characteristics of an HP turbine stage is not well understood, however. A combustor swirl simulator has been designed and commissioned in the Oxford Turbine Research Facility (OT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…The results show a significant impact on performance, almost equal to superimposed swirl. Qureshi et al [6] observed a great impact of swirl orientation and clocking on endwall heat transfer: both a significant increase or a slight decrease in Nusselt numbers can occur. They determine local divergence and convergence of wall streamlines and as a consequence, an accumulation or dissipation of boundary layer fluid to be responsible.…”
Section: Combustor-turbine Interactionmentioning
confidence: 99%
“…The results show a significant impact on performance, almost equal to superimposed swirl. Qureshi et al [6] observed a great impact of swirl orientation and clocking on endwall heat transfer: both a significant increase or a slight decrease in Nusselt numbers can occur. They determine local divergence and convergence of wall streamlines and as a consequence, an accumulation or dissipation of boundary layer fluid to be responsible.…”
Section: Combustor-turbine Interactionmentioning
confidence: 99%
“…It is feasible to predict the accuracy of numerical calculation through qualitative comparison [25]. Qureshi et al [14], from Oxford University, carried out aerodynamics and heat transfer experiments and predictions in the MT1 turbine blades, and the shape and working condition of the MT1 turbine are very similar to the S2 blade in this study. By comparing the numerical simulation data with this experimental data, a reasonable calculation accuracy can be obtained.…”
Section: Experimental Validation Of Numerical Modelsmentioning
confidence: 93%
“…This ratio is not random, but is based on relevant research. In the study of Qureshi et al [14] and Ameni et al [16], specific studies of this ratio are given. Non-adiabatic heat transfer numerical simulation models usually use isothermal wall conditions, and the wall temperature depends on the heat transfer between the wall and the main flow.…”
Section: Turbine In Study and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors have studied the isolated effects of inlet swirl (Giller et al [14], Qureshi et al [15], Schmid et al [16], Beard et al [17], Insinna et al [18], and Jacobi et al [19]), hot streaks (He et al [20], Basol et al [21], and Beard et al [22]) and elevated turbulence (van Fossen et al [23]). However, there are few data, and no unifying theory exists with respect to their combined effects.…”
Section: Introductionmentioning
confidence: 99%